Capillary pathology with prominent basement membrane reduplication is the hallmark histopathological feature of scleromyositis. (12th August 2022) - Ellezam, Benjamin; Leclair, Valérie; Troyanov, Yves; Bersali, Imane; Giannini, Margherita; Hoa, Sabrina; Bourré‐Tessier, Josiane; Nadon, Valérie; Drouin, Julie; Karamchandani, Jason; O'Ferrall, Erin; Lannes, Béatrice; et al.
Abstract: Aims: We aim to perform ultrastructural and histopathological analysis of muscle biopsies from a large group of systemic sclerosis (SSc) patients, including some with early/mild SSc features, and examine whether capillary pathology differentiates 'scleromyositis' (SM) from other auto‐immune myositis (AIM) subsets. Methods: Muscle biopsies from a total of 60 SM patients and 43 AIM controls from two independent cohorts were examined by electron microscopy, collagen‐4 immunofluorescence (Col4IF) and routine light microscopy. Results: Ultrastructural examination revealed prominent capillary basement membrane (BM) reduplication (4+ layers in >50% of capillaries) in 65% of SM vs 0% of AIM controls ( p  < 0.001). In SM cases without prominent BM reduplication, capillary dilation was the most distinctive feature, present in 8% of capillaries in SM vs 2% in controls ( p  = 0.001). Accumulation of ensheathed pericyte processes was another characteristic feature of SM and closely correlated with the degree of BM reduplication ( r  = 0.833, p <  0.001). On light microscopy, BM marker Col4IF revealed more frequent capillary enlargement in SM than in controls (84% vs 21%, p <  0.001). SM cases were classified as non‐inflammatory myopathy (36%), non‐specific myositis (33%) or immune‐mediated necrotizing myopathy (31%), but despite this histopathological heterogeneity, prominent BM reduplication remained a constant finding. In the 16 SM patients with early/mild SSc features, 63% showed prominent BM reduplication. Conclusions: These results show that capillary pathology, and in particular prominent capillary BM reduplication, is the hallmark histopathological feature of SM even in patients with early/mild SSc and support the concept of SM as an organ manifestation of SSc and a distinct subset of AIM. Abstract : We have proposed defining muscle involvement in systemic sclerosis as 'scleromyositis' to better capture the full spectrum of patients including those with predominant muscle disease and only mild skin involvement. Prominent capillary basement membrane reduplication on muscle biopsy is a frequent finding in scleromyositis, even in patients with early or mild skin disease, and is rarely seen in other myositis subsets, supporting the concept of scleromyositis as an organ manifestation of systemic sclerosis and a distinct subset of auto‐immune myositis.